A wideband quadrature power splitter covering 81.75% fractional bandwidth in single layer via‐less technology. Issue 1 (January 2017) - Lucarelli, Matteo; Maddio, Stefano; Collodi, Giovanni; Cidronali, Alessandro
ABSTRACT: A novel 90° wideband quadrature power splitter configuration based on the contemporary use of a large band 3‐dB Wilkinson power divider combined with a 90 degrees Schiffman phase shifter is presented. The proposed approach is consistent with an implementation on a single layer, via‐less, low performance substrate, thus enabling simple fabrication and integration. The proposed solution leads to a balanced power splitting (±1.5 dB), a consistent phase shifting (90°±10°), and a good input matching ( S 11  ≤ −10 dB) from 2.3 GHz to 5.48 GHz, hence suitable for a wide range of applications, comprising IEEE 802.11 WiFi operation in both S and C band. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:142–145, 2017